(untitled) (Jurnal Kemanusiaan, 2022)
Suicide is the second leading cause of death for young people ranging from the age of 15 to 29 years old. To date, it has been little research that studied the psychological risk factors correlated with suicidal ideation among undergraduate students. Therefore, the purpose of this study was to identify the level of suicidal ideation and psychological risk factors (depression, anxiety, stress, academic stress and hopelessness), to examine the relationship between suicidal ideation and psychological risk factors and to determine whether these psychological risk factors predict suicidal ideation among undergraduate students. This quantitative study was conducted through correlational research design which involves 375 undergraduate students from a Malaysian public university in Johor, Malaysia and respondents were selected via proportional stratified random sampling method. Online questionnaire was distributed in getting the information from the samples. Descriptive statistics and inferential statistics (Pearson correlation and multiple regression) were applied to analyse the collected data using SPSS software. The findings showed that the level of depression, anxiety and suicidal ideation is low while the level of stress, academic stress and hopelessness is moderate. Findings revealed that there was significant relationship between suicidal ideation and psychological risk factors. Results also found that depression, stress, and hopelessness were found to be the significant predictors of suicidal ideation while anxiety and academic stress did not predict suicidal ideation. This study provides an implication to various parties especially to university students, parents, lecturers.